Segurança no trânsito em Minas Gerais: da inserção na agenda ao formalismo no planejamento - Rocha, Natália de Carvalho (2015)
Road traffic accidents are among the leading causes of death in the world, a situation that is exacerbated in low and middle-income countries, according to the World Health Organization (WHO). In this scenario, the United Nations General Assembly proclaimed the period 2011¬ 2020 as the "Decade of Action for Road Safety" and recommended to member countries to draw up national, regional and local plans to guide their actions in the decade. In this sense, in Brazil, the National Mobilization Committee for Health, Safety and Peace in Traffic, prepared and approved on August 10, 2011, the "National Plan to Reduce Accidents and Road Safety for the decade 2011-2020" that besides presenting problems in their formulation, is stopped at the Civil House awaiting the signature of the President. In Minas Gerais, was drawn up the "Mineiro Plan for the Prevention and Treatment of Traffic Accidents" (PMPAATT), which was established by State Decree no. 45.466 of September 1, 2010, and also was never implemented. What exists in practice, both at the national and state levels, are fragmented actions for road safety that occurs despite the plans that were elaborated. Thus, the aim of this study is to examine how the road safety theme is included in the agenda of the state government and the possible factors that contributed to its non execution. Therefore, a contextualization of the problem is made by drawing a panoramic view of the situation for the road safety at global, national and state level. It is then held a template literature review of the Public Policy Cycle and the conventional design of Governmental Planning, which will support the analysis of PMPAATT.